The Role of Orientalists in The Quran and Hadith: Liberalization and Hermeneutics - Azni Lubis, Muhammad Jihad; Siregar, Fahmi Randa (Journal of Strategy and Transformation in Educational Management, 2025)
Orientalists when viewed from the epistemological aspect, then "pure Science" or religion as the object of research is the basis for the West (Orientalists) in studying Islam using several methods of approach, namely the historicism approach, the phenomenological approach, and the theological approach. Orientalists when viewed from the axiological aspect, then behind their study of Islam there is a certain motivation or goal that they want to achieve. These motivations are Religious motivation, namely the spread of Christianity, Imperialism motivation, namely controlling the eastern or Islamic world including its natural resources (business) and political influence, and scientific motivation, namely studying Islam by viewing Islam as an object of scientific study. Orientalists can also be recognized through their objects of study, namely Orientalists who study the Qur'an and Orientalists who study the Hadith, the focus of their analysis is more focused on the history of its codification and historical facts that are considered to accompany the text, without paying attention to the essence and practices of Muslims. The existence of research results, studies, and analysis of orientalists has caused different reactions for "Muslim intellectuals", some are against it and some are neutral even though they know that many orientalist conclusions are not true. What is clear is that they study Islam using Methodology, in the author's opinion this is the most important part that needs to be captured by Muslim scholars.